THE APPLICATION OF QUANTUM TEACHING WITH MODEL FOR THE FOURTH GRADE STUDENTS OF SD NEGERI 7 KUTOSARI IN THE ACADEMIC YEAR OF 2015/2016 - Suningsih, Nita (KALAM CENDEKIA PGSD KEBUMEN, 2016)
The objectives of this research are to describe the steps on the application of Quantum Teaching with model, to improve Mathematics learning about geometry, and to describe problems and solutions in the application of Quantum Teaching with model. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 35 students. The results of this research show that the application of Quantum Teaching with media can improve Mathematics learning about geometry. It was proven by the increase of learning outcomes in the first cycle 71.43%, in the second cycle 81.43%, and in the third cycle 88.57%. The application of Quantum Teaching in Mathematics learning encountered some problems but those problems can be solved through some solutions. The conclusion of this research the application of Quantum Teaching with model can improve Mathematics learning about geometry for the fourth grade students of SD Negeri 7 Kutosari in the academic year of 2015/2016. Keywords: Quantum Teaching model, students? learning outcomes, geometry